Robotics Reduces Radiation Exposure in Minimally Invasive Lumbar Fusion Compared With Navigation. Issue 18 (15th September 2022) - Shahi, Pratyush; Vaishnav, Avani; Araghi, Kasra; Shinn, Daniel; Song, Junho; Dalal, Sidhant; Melissaridou, Dimitra; Mai, Eric; Dupont, Marcel; Sheha, Evan; Dowdell, James; Iyer, Sravisht; et al.
Abstract : Study Design: Retrospective cohort. Objective: To compare robotics and navigation for minimally invasive elective lumbar fusion in terms of radiation exposure and time demand. Summary of Background Data: Although various studies have been conducted to demonstrate the benefits of both navigation and robotics over fluoroscopy in terms of radiation exposure, literature is lacking in studies comparing robotics versus navigation. Materials and Methods: Patients who underwent elective one-level or two-level minimally invasive transforaminal lumbar interbody fusion (TLIF) by a single surgeon using navigation (Stryker SpineMask) or robotics (ExcelsiusGPS) were included (navigation 2017–2019, robotics 2019–2021, resulting in prospective cohorts of consecutive patients for each modality). All surgeries had the intraoperative computed tomography workflow. The two cohorts were compared for radiation exposure [fluoroscopy time and radiation dose: image capture, surgical procedure, and overall) and time demand (time for setup and image capture, operative time, and total operating room (OR) time]. Results: A total of 244 patients (robotics 111, navigation 133) were included. The two cohorts were similar in terms of baseline demographics, primary/revision surgeries, and fusion levels. For one-level TLIF, total fluoroscopy time, total radiation dose, and % of radiation for surgical procedure were significantly less with robotics compared with navigation (20 vs. 25 s, P <0.001; 38 vs. 42 mGy, P =0.05; 58% vs. 65%, P =0.021). Although time for setup and image capture was significantly less with robotics (22 vs. 25 min, P <0.001) and operative time was significantly greater with robotics (103 vs. 93 min, P <0.001), there was no significant difference in the total OR time (145 vs. 141 min, P =0.25). Similar findings were seen for two-level TLIF as well. Conclusion: Robotics for minimally invasive TLIF, compared with navigation, leads to a significant reduction in radiation exposure both to the surgeon and patient, with no significant difference in the total OR time.